Titanium dioxide-based positive electrode material for aqueous zinc ion battery and preparation method and application of titanium dioxide-based positive electrode material
The titanium dioxide and carbon composite materials that synthesize and introduce metal elements through the solvent-thermal method solves the problem of insufficient performance of the positive electrode material of the aqueous zinc ion battery, significantly improves the storage capacity and kinetic performance of zinc ions, and achieves high specific capacity and rapid reaction .
Patent Information
- Application Number
- CN202411361400.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-03
AI Technical Summary
The cathode material of aqueous zinc ion batteries faces complex phase transformation, structural deterioration, dissolution and low efficiency, resulting in poor performance. In particular, titanium dioxide materials have hindered zinc ions due to electrostatic repulsion, which is difficult to meet practical application requirements.
The titanium-based metal organic frame material was synthesized by solvothermal method, metal elements were introduced to regulate coordination nodes, and pyrolysis was carried out under an inert atmosphere to form a composite material of titanium dioxide and carbon, inhibit the crystallization and grain growth of titanium dioxide, and build an atomic level Compound interface to improve zinc ion storage capacity and kinetic performance.
By introducing metal elements, the overall performance of zinc ion batteries is significantly improved, the storage capacity and transmission efficiency of zinc ions are enhanced, the specific capacity is improved, and the problems of low utilization rate of existing materials and slow kinetic reactions are solved.
Smart Images

Figure CN119240784A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite material preparation and battery material, and specifically relates to a titanium dioxide-based positive electrode material for an aqueous zinc ion battery and a preparation method and application thereof. Background Art
[0002] Due to safety and cost limitations, lithium-ion batteries are unable to meet the growing needs of the energy storage market. Relatively speaking, aqueous zinc-ion batteries have become an ideal choice for large-scale energy storage devices due to their inherent advantages such as high safety, low cost and high energy density. However, during the use of aqueous zinc-ion batteries, their positive electrode materials (such as manganese, vanadium-based materials and Prussian blue analogs) often face a series of challenges such as complex phase changes, structural degradation, dissolution and low efficiency, which seriously restrict their performance.
[0003] In order to overcome the above challenges, it is particularly important to design and develop new high-performance cathode materials. Titanium dioxide has been widely used in photocatalysis, sensors, rechargeable batteries and solar cells due to its advantages in chemical stability, cost-effectiveness and environmental friendliness. However, there are still huge challenges in using titanium dioxide as a cathode material for aqueous zinc-ion batteries. This is because titanium dioxide has a relatively narrow crystal structure and has a strong electrostatic repulsion effect on zinc ions, which makes it difficult for its specific capacity and kinetic performance to meet practical application requirements. Therefore, it is necessary to develop a new titanium dioxide-based cathode material for aqueous zinc-ion batteries. Summary of the invention
[0004] In view of some deficiencies in the prior art, the present invention provides a titanium dioxide-based positive electrode material for an aqueous zinc ion battery, and a preparation method and application thereof. The present invention firstly adopts a solvothermal method to synthesize a titanium-based metal organic framework material, regulates coordination nodes by introducing different metal elements, and then pyrolyzes the titanium dioxide-based positive electrode material under an inert atmosphere to obtain the titanium dioxide-based positive electrode material for an aqueous zinc ion battery. The titanium dioxide-based positive electrode material for an aqueous zinc ion battery is a composite material of titanium dioxide and carbon, the introduced metal elements promote the formation of titanium vacancies in titanium dioxide crystals, effectively inhibit its crystallization and grain growth, titanium dioxide nanoparticles and carbon skeletons together form a continuous conductive network and rich heterogeneous interfaces, and the zinc ion storage capacity and kinetic performance of the material are significantly improved through atomic-level interface contact and enhanced interface interaction, thereby effectively improving the overall performance of the battery, and having good practicality.
[0005] In order to achieve the above technical objectives, the present invention adopts the following technical means:
[0006] The present invention first provides a method for preparing a titanium dioxide-based positive electrode material for an aqueous zinc ion battery, the preparation method comprising:
[0007] (1) adding metal nitrate to a mixed solvent containing N,N-dimethylformamide and anhydrous methanol, and then adding titanium alkoxide and an organic ligand thereto, stirring until the mixture is uniformly dispersed to obtain a mixed solution;
[0008] The obtained mixed solution is subjected to a solvothermal reaction, and after the reaction is completed, it is centrifuged, washed, and vacuum dried to obtain a pure titanium-based metal organic framework material;
[0009] (2) placing the obtained titanium-based metal organic framework material in a tubular furnace and performing heat treatment under the protection of an inert gas to obtain the titanium dioxide-based positive electrode material for the aqueous zinc ion battery.
[0010] Preferably, in step (1), in the mixed solvent containing N,N-dimethylformamide and anhydrous methanol, the volume ratio of N,N-dimethylformamide to anhydrous methanol is 1:1 to 9:1.
[0011] Preferably, in step (1), the metal nitrate comprises one or more of ferric nitrate nonahydrate, cobalt nitrate hexahydrate, and zinc nitrate hexahydrate;
[0012] The titanium alkoxide includes one of isopropyl titanate and tetrabutyl titanate;
[0013] The organic ligand includes any one of 2-aminoterephthalic acid and terephthalic acid.
[0014] Preferably, in step (1), the molar ratio of the titanium alkoxide to the organic ligand is 1:2 to 1:4; the molar ratio of the metal nitrate to the titanium alkoxide is 0 to 1:9 and is not 0.
[0015] Preferably, in step (1), the solvent thermal reaction is carried out at 150° C. for 16 to 72 hours.
[0016] Preferably, in step (2), the heat treatment conditions are: the temperature of the tube furnace is raised to 300°C at a rate of 1-2°C / min and maintained for 4 hours, then raised to 600°C at a rate of 5°C / min and maintained at this temperature for 2 hours.
[0017] The present invention also provides a titanium dioxide-based positive electrode material for an aqueous zinc ion battery prepared by the above method. The titanium dioxide-based positive electrode material for an aqueous zinc ion battery is a composite material composed of titanium dioxide and carbon, comprising a carbon skeleton and titanium dioxide nanoparticles uniformly embedded in the carbon skeleton; metal elements are introduced into the titanium dioxide-based positive electrode material for an aqueous zinc ion battery to inhibit the growth of titanium dioxide grains, so that an atomic-level composite interface is formed between the titanium dioxide nanoparticles and the carbon skeleton; and a large number of titanium vacancies are generated on the titanium dioxide nanoparticles after being doped with metal elements.
[0018] The present invention also provides the use of the above-mentioned titanium dioxide-based positive electrode material for aqueous zinc ion batteries in batteries.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] (1) The present invention has successfully developed a positive electrode material for aqueous zinc ion batteries, namely, a titanium dioxide-based positive electrode material. The material is a composite material of titanium dioxide and carbon prepared by an in-situ pyrolysis method of a metal organic framework. The method not only has a simple process flow, but also has good structural consistency and interface compatibility. By adjusting the coordination chemical parameters and optimizing the synthesis conditions (such as adjusting the metal coordination nodes, controlling the reaction temperature, etc.), precise control of its components, structure, interface and other properties can be achieved. The present invention introduces other metal elements in the synthesis process of the titanium-based metal organic framework. These elements occupy the coordination nodes of titanium and inhibit the crystallization and grain growth of titanium dioxide in the subsequent pyrolysis process. By optimizing the amount of metal elements and parameters such as reaction temperature and time, the grain size of titanium dioxide can be controlled to a few nanometers or even sub-nanometers, thereby constructing an atomic-level composite interface between titanium dioxide and carbon, significantly enhancing the interface's storage capacity for zinc ions. In addition, the introduced metal elements are doped into the titanium dioxide lattice during the pyrolysis process, resulting in the formation of a large number of titanium vacancies, which provide additional active sites for zinc ion storage. This unique zinc ion storage method with the help of interfaces and titanium vacancies enables titanium dioxide to be effectively used as the positive electrode material of aqueous zinc ion batteries, providing key technical support for the further development of this technology field.
[0021] (2) The energy storage mechanism of the titanium dioxide-based positive electrode material in the present invention is dominated by the interfacial space charge storage mechanism. The material has abundant atomic-level interfaces, which causes the zinc ions and electrons to be decoupled and transmitted at the interface between titanium dioxide and carbon, that is, at the interface, the zinc ions are stored on the side close to the titanium dioxide, while the electrons are stored on the side close to the carbon material. This mechanism not only greatly expands the internal storage space of the material, but also significantly improves the transmission efficiency of zinc ions. On the contrary, due to the insufficient number of interfaces in the existing material system, the zinc ion energy storage is mainly dominated by bulk storage, that is, the zinc ions are embedded in the crystal structure of titanium dioxide by diffusion. However, due to the relatively narrow crystal structure of titanium dioxide, it has a strong electrostatic repulsion effect on zinc ions, resulting in low utilization of active materials and slow reaction kinetics. The present invention effectively solves the problems of low utilization of positive electrode materials and slow kinetic reactions in the existing system mechanism, and provides key technical advantages for improving battery performance.
[0022] (3) The specific capacity of the titanium dioxide-based positive electrode material in the present invention is as high as 104 mAh / g at a current density of 0.1 A / g, which is better than the 14 mAh / g of titanium dioxide positive electrode material using the traditional bulk mechanism.
[0023] The application field of the present invention is not limited to aqueous zinc ion battery positive electrode materials, but is also applicable to other battery systems. In addition, the technology can also be widely used in multiple fields such as optics, electronics and catalysis. This wide applicability provides the present invention with a broader market potential and application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 X-ray diffraction patterns of iron-doped and undoped titanium dioxide and carbon composites.
[0025] Figure 2 Structural diagrams of iron-doped and undoped titanium dioxide and carbon composites: (a) Transmission electron microscopy photograph of iron-doped titanium dioxide and carbon composites; (b) Transmission electron microscopy photograph of undoped titanium dioxide and carbon composites; (c) High-resolution transmission electron microscopy photograph of iron-doped titanium dioxide and carbon composites; (d) Atomic-level high-resolution transmission electron microscopy photograph of iron-doped titanium dioxide and carbon composites.
[0026] Figure 3 Cyclic voltammetry curve of iron-doped titanium dioxide and carbon composite material.
[0027] Figure 4 The cycling performance diagram of iron-doped and undoped titanium dioxide and carbon composites and titanium dioxide positive electrode materials using bulk mechanism.
[0028] Figure 5 Energy storage mechanism diagram of iron-doped titanium dioxide and carbon composite materials: (a) fitting curve of the relationship between the Ln function of charge and voltage, (b) fitting curve of the relationship between charge-voltage function and charge.
[0029] Figure 6 Structural diagram and performance diagram of cobalt-doped titanium dioxide and carbon composite materials: (a) transmission electron microscope photo; (b) cycle performance diagram, where the current density is 0.1A / g and the voltage range is 0.2~1.8V.
[0030] Figure 7 Structural diagram and performance diagram of zinc-doped titanium dioxide and carbon composite materials: (a) transmission electron microscope photo; (b) cycle performance diagram, where the current density is 0.1A / g and the voltage range is 0.2~1.8V.
[0031] Figure 8The structural diagram and performance diagram of titanium dioxide and carbon composite materials: (a) transmission electron microscope photo; (b) cycle performance diagram, where the current density is 0.1A / g and the voltage range is 0.2~1.8V. DETAILED DESCRIPTION
[0032] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited thereto.
[0033] Example 1: Preparation of titanium dioxide-based positive electrode materials for aqueous zinc ion batteries
[0034] (1) 126 mg of ferric nitrate nonahydrate and 830 μL of isopropyl titanate were added to a mixed solvent consisting of 20 mL of N,N-dimethylformamide and 20 mL of anhydrous methanol, and then 1.014 g of 2-aminoterephthalic acid was added. The mixture was stirred for 0.5 h to obtain a mixed solution.
[0035] The mixed solution was transferred to a 50 mL hydrothermal reactor and subjected to solvent thermal reaction at 150 °C for 16 hours. After the reaction, the product was washed three times with N,N-dimethylformamide and anhydrous methanol, and then dried in a vacuum oven at 80 °C for 12 hours to obtain a pure titanium-based metal-organic framework material.
[0036] (2) The obtained titanium-based metal organic framework material is placed in the center of a tubular furnace, the air in the furnace is evacuated and filled with high-purity nitrogen, the heating rate is set to 2°C / min, the temperature is raised to 300°C and maintained for 4 hours; then the temperature is further raised to 600°C at a rate of 5°C / min and kept warm for 2 hours. After the insulation is completed, the tubular furnace is naturally cooled to room temperature to obtain the titanium dioxide-based positive electrode material for the aqueous zinc ion battery, which is recorded as an iron-doped titanium dioxide and carbon composite material.
[0037] The same experimental process as above is adopted, but iron nitrate nonahydrate is not added in step (1). The titanium dioxide-based positive electrode material for aqueous zinc ion battery obtained thereby is recorded as undoped titanium dioxide and carbon composite material.
[0038] Figure 1 The X-ray diffraction diagram of iron-doped and undoped titanium dioxide and carbon composite materials. It can be seen from the figure that compared with the sample without the introduction of iron, the X-ray diffraction peak intensity of the sample with the introduction of iron is significantly reduced, and the peak width is increased, indicating that the introduction of iron effectively inhibits the crystallization and grain growth of titanium dioxide.
[0039] Figure 2 The structure diagram of iron-doped and undoped titanium dioxide and carbon composite materials. Figure 2As can be seen in a, in the iron-doped titanium dioxide and carbon composite material, titanium dioxide nanoparticles are uniformly embedded in the carbon skeleton, and their size is between 2 and 5 nanometers. In the undoped titanium dioxide and carbon composite material ( Figure 2 b), the titanium dioxide nanoparticles are mainly distributed at the edge of the carbon skeleton, and their size is greater than 10 nanometers. It can be seen that the iron element effectively suppresses the grain size of titanium dioxide and promotes its uniform distribution. Figure 2 c shows the high-resolution transmission electron microscopy image of the iron-doped titanium dioxide and carbon composite material, which shows that an atomic-level composite interface is formed between the titanium dioxide nanoparticles and the carbon skeleton. Figure 2 d is the intensity change of the titanium atom array of titanium dioxide grains in the iron-doped titanium dioxide and carbon composite material, indicating the existence of titanium vacancies in titanium dioxide.
[0040] In this embodiment, the iron-doped titanium dioxide and carbon composite material is made into a positive electrode of a zinc ion battery and assembled into a button battery for performance testing. Figure 3 The cyclic voltammetry curve of the battery is shown in Figure 2. The scan rate is 0.2 mV / s and the voltage range is 0.2-1.8 V (relative to Zn 2+ A pair of redox peaks appearing at 0.75 / 0.95 V in the curve indicate the reversible insertion / extraction of zinc ions in the material.
[0041] Figure 4 The cycling performance diagrams of iron-doped and undoped titanium dioxide and carbon composite materials and titanium dioxide positive electrode materials using a bulk mechanism are shown. The results show that the specific capacity of the iron-doped titanium dioxide and carbon composite material exceeds 100mAh / g at a current density of 0.1A / g, which is significantly better than the undoped titanium dioxide and carbon composite material (specific capacity of 50mAh / g) and the titanium dioxide positive electrode material using a bulk mechanism (specific capacity of 14mAh / g) under the same conditions.
[0042] Figure 5 Figure 2 shows the energy storage mechanism of iron-doped titanium dioxide and carbon composites. Figure 5 It can be observed in (a) that the power law exponent n is 4 in the smaller charge range, which is consistent with the expected range of 3 to 4, while there is a deviation in the larger charge range. Figure 5 (b) shows that when the charge exceeds 20 mAh / g, the function shows a linear relationship with the charge. In addition, the γ values when n=3 and n=4 are 0.310 and 0.302 g / mAh, respectively, which are close to the theoretical values. These data indicate that in the voltage range of 0.2 to 1.8 V, the energy storage mechanism of the battery is mainly dominated by the interfacial space charge storage mechanism.
[0043] Example 2: Preparation of titanium dioxide-based positive electrode materials for aqueous zinc ion batteries
[0044] (1) 43 mg of cobalt nitrate hexahydrate and 830 μL of isopropyl titanate were added to a mixed solvent consisting of 20 mL of N,N-dimethylformamide and 20 mL of anhydrous methanol, and then 1.014 g of 2-aminoterephthalic acid was added. The mixture was stirred for 0.5 h to obtain a mixed solution.
[0045] The mixed solution was transferred to a 50 mL hydrothermal reactor and subjected to solvent thermal reaction at 150 °C for 16 hours. After the reaction, the product was washed three times with N,N-dimethylformamide and anhydrous methanol, and then dried in a vacuum oven at 70 °C for 16 hours to obtain a pure titanium-based metal-organic framework material.
[0046] (2) The obtained titanium-based metal organic framework material is placed in the center of a tubular furnace, the air in the furnace is evacuated and filled with high-purity nitrogen, the heating rate is set to 1°C / min, the temperature is raised to 300°C and maintained for 4 hours; then the temperature is further raised to 600°C at a rate of 5°C / min and kept warm for 2 hours. After the insulation is completed, the tubular furnace is naturally cooled to room temperature to obtain the titanium dioxide-based positive electrode material for the aqueous zinc ion battery, which is recorded as a cobalt-doped titanium dioxide and carbon composite material.
[0047] Figure 6 Transmission electron microscope images and electrochemical performance diagrams of cobalt-doped titanium dioxide and carbon composite materials. It can be seen from the figure that cobalt-doped titanium dioxide and carbon composite materials have similar structures to iron-doped titanium dioxide and carbon composite materials, and their specific capacity can reach up to 92 mAh / g at a current density of 0.1 A / g.
[0048] Example 3: Preparation of titanium dioxide-based positive electrode materials for aqueous zinc ion batteries
[0049] (1) 92 mg of zinc nitrate hexahydrate and 830 μL of isopropyl titanate were added to a mixed solvent consisting of 20 mL of N,N-dimethylformamide and 20 mL of anhydrous methanol, and then 1.014 g of 2-aminoterephthalic acid was added. The mixture was stirred for 0.5 h to obtain a mixed solution.
[0050] The mixed solution was transferred to a 50 mL hydrothermal reactor and subjected to solvent thermal reaction at 150 °C for 16 hours. After the reaction, the product was washed three times with N,N-dimethylformamide and anhydrous methanol, and then dried in a vacuum oven at 90 °C for 10 hours to obtain a pure titanium-based metal-organic framework material.
[0051] (2) The obtained titanium-based metal organic framework material is placed in the center of a tubular furnace, the air in the furnace is evacuated and filled with high-purity nitrogen, the heating rate is set to 2°C / min, the temperature is raised to 300°C and maintained for 4 hours; then the temperature is further raised to 600°C at a rate of 5°C / min and kept warm for 2 hours. After the insulation is completed, the tubular furnace is naturally cooled to room temperature to obtain the titanium dioxide-based positive electrode material for the aqueous zinc ion battery, which is recorded as zinc-doped titanium dioxide and carbon composite material.
[0052] Figure 7 The transmission electron microscope image and electrochemical performance diagram of zinc-doped titanium dioxide and carbon composite materials. It can be seen from the figure that zinc-doped titanium dioxide and carbon composite materials have similar structures to iron-doped titanium dioxide and carbon composite materials, and their specific capacity can reach up to 61mAh / g at a current density of 0.1A / g.
[0053] Comparative Example 1:
[0054] (1) 511 μL of tetrabutyl titanate was added to a mixed solvent consisting of 18 mL of N,N-dimethylformamide and 2 mL of anhydrous methanol, and then 997 mg of terephthalic acid was added. The mixture was stirred for 0.5 h to obtain a mixed solution.
[0055] The mixed solution was transferred to a 50 mL hydrothermal reactor and subjected to solvent thermal reaction at 150 °C for 72 hours. After the reaction, the product was washed three times with N,N-dimethylformamide and anhydrous methanol, and then dried in a vacuum oven at 90 °C for 12 hours to obtain a pure titanium-based metal-organic framework material.
[0056] (2) The obtained titanium-based metal organic framework material is placed in the center of a tubular furnace, the air in the furnace is evacuated and filled with high-purity nitrogen, the heating rate is set to 1°C / min, the temperature is raised to 300°C and maintained for 4 hours; then the temperature is further raised to 600°C at a rate of 5°C / min and kept warm for 2 hours. After the insulation is completed, the tubular furnace is naturally cooled to room temperature to obtain the titanium dioxide-based positive electrode material for the aqueous zinc ion battery, which is recorded as a titanium dioxide and carbon composite material.
[0057] Figure 8 The transmission electron microscope image and electrochemical performance diagram of titanium dioxide and carbon composite material. It can be seen from the figure that the titanium dioxide nanoparticles have a high degree of crystallization and their size is about 8 nanometers. There is obvious phase separation between titanium dioxide nanoparticles and carbon skeletons, and the interface composite effect between the two is poor. Its specific capacity is up to 44mAh / g at a current density of 0.1A / g, which is significantly lower than that of iron-doped titanium dioxide and carbon composite materials.
[0058] In summary, in the titanium dioxide-based positive electrode material for the aqueous zinc ion battery described in the present invention, titanium dioxide nanoparticles and the carbon skeleton together constitute a continuous conductive network and rich heterogeneous interfaces, which significantly improve the zinc ion storage capacity and kinetic performance of the material through atomic-level interface contact and enhanced interface interaction, thereby effectively improving the overall performance of the battery and having good practicality.
[0059] The embodiments are preferred implementations of the present invention, but the present invention is not limited to the above-mentioned implementations. Any obvious improvements, substitutions or modifications that can be made by those skilled in the art without departing from the essential content of the present invention belong to the protection scope of the present invention.
Claims
1. A method for preparing a titanium dioxide-based positive electrode material for an aqueous zinc ion battery, characterized in that: The preparation method comprises: (1) adding metal nitrate to a mixed solvent containing N,N-dimethylformamide and anhydrous methanol, and then adding titanium alkoxide and an organic ligand thereto, stirring until the mixture is uniformly dispersed to obtain a mixed solution; The obtained mixed solution is subjected to a solvothermal reaction, and after the reaction is completed, it is centrifuged, washed, and vacuum dried to obtain a pure titanium-based metal organic framework material; (2) placing the obtained titanium-based metal organic framework material in a tubular furnace and performing heat treatment under the protection of an inert gas to obtain the titanium dioxide-based positive electrode material for the aqueous zinc ion battery.
2. The method for preparing a titanium dioxide-based positive electrode material for an aqueous zinc ion battery according to claim 1, wherein: In step (1), in the mixed solvent containing N,N-dimethylformamide and anhydrous methanol, the volume ratio of N,N-dimethylformamide to anhydrous methanol is 1:1 to 9:
1.
3. The method for preparing a titanium dioxide-based positive electrode material for an aqueous zinc ion battery according to claim 1, wherein: In step (1), the metal nitrate includes one or more of ferric nitrate nonahydrate, cobalt nitrate hexahydrate, and zinc nitrate hexahydrate.
4. The method for preparing a titanium dioxide-based positive electrode material for an aqueous zinc ion battery according to claim 1, wherein: In step (1), the titanium alkoxide includes one of isopropyl titanate and tetrabutyl titanate.
5. The method for preparing a titanium dioxide-based positive electrode material for an aqueous zinc ion battery according to claim 1, wherein: In step (1), the organic ligand includes any one of 2-aminoterephthalic acid and terephthalic acid.
6. The method for preparing a titanium dioxide-based positive electrode material for an aqueous zinc ion battery according to claim 1, wherein: In step (1), the molar ratio of the titanium alkoxide to the organic ligand is 1:2 to 1:4; the molar ratio of the metal nitrate to the titanium alkoxide is 0 to 1:9 and is not 0.
7. The method for preparing a titanium dioxide-based positive electrode material for an aqueous zinc ion battery according to claim 1, wherein: In step (1), the solvent thermal reaction conditions are: reaction at 150° C. for 16 to 72 hours.
8. The method for preparing a titanium dioxide-based positive electrode material for an aqueous zinc ion battery according to claim 1, wherein: In step (2), the heat treatment conditions are as follows: the temperature of the tube furnace is raised to 300°C at a rate of 1-2°C / min and maintained for 4 hours, then raised to 600°C at a rate of 5°C / min and maintained at this temperature for 2 hours.
9. A titanium dioxide-based positive electrode material for aqueous zinc ion batteries prepared by the method according to any one of claims 1 to 8, characterized in that: The titanium dioxide-based positive electrode material for an aqueous zinc ion battery is a composite material composed of titanium dioxide and carbon, which comprises a carbon skeleton and titanium dioxide nanoparticles uniformly embedded in the carbon skeleton; metal elements are introduced into the titanium dioxide-based positive electrode material for an aqueous zinc ion battery to inhibit the growth of titanium dioxide grains, so that an atomic-level composite interface is formed between the titanium dioxide nanoparticles and the carbon skeleton; and a large number of titanium vacancies are generated by the titanium dioxide nanoparticles after being doped with metal elements.
10. Use of the titanium dioxide-based positive electrode material for aqueous zinc ion batteries according to claim 9 in batteries.
